Promising trends in agricultural practices towards food security: expanding the desert landscape and flora into mainstream farming - Berwal, Mukesh Kumar; Deepa, P. R.; Sharma, Pankaj Kumar (Frontiers in Agronomy, 2025)
Rapid climate change and degrading quality of once-fertile agricultural lands makes it imperative to turn attention towards marginal and desert lands for practice of farming. Additionally, wild xerophytes (desert plants) have been successfully thriving on such lands of extreme temperatures and water scarcity, and provide important clues for traits desired in food crops (such as stress tolerance). In past, the local human communities have derived nutrition from the underexplored (semi)arid plants during drought and famine. Latest technological innovations like application of clay nanoparticles and xerophyte-derived rhizobacteria, vertical farming, horticulture crop-based site management, and restoration of degraded agricultural lands using native and climate-resilient plant varieties offer a glimpse of hope. Therefore, (i) farming of popular food crops (like Solanum lycopersicum using techniques like drip irrigation) on desert lands, as well as, (ii) bringing desert plants (such as the superior varieties of tree legumes like Prosopis cineraria) into mainstream agriculture are two approaches that have shown promise. These actions would also align with the UN Sustainable Development Goals, viz.: SDG 2 (Zero hunger), SDG 12 (Responsible consumption and production) and SDG 13 (Climate action) in particular. Through the current article, we intend to highlight recent success stories on desert landscapes/plants and present the way forward for sustainable agriculture in future.